Determinants of hygienic handling of food by consumers in the COVID-19 pandemic context: A cross-sectional study in Vietnam - DANG,Huy Duc (2022)
Abstract The objectives of this research are trifold. The first is to unveil antecedents of food-handling behaviors in the context of the COVID-19 pandemic. The second is to investigate the consistency of impacts of proposed determinants across different handling behaviors. The third is to confirm whether or not the premise of intention as the sole direct determinant of behavior in the Theory of Planned Behavior (TPB) holds. As such, TPB served as the guiding theory, and Factor Analysis and Seemingly Unrelated Regression were used for data analysis. The results discuss the discrepancy of impacts between heterogeneous food-handling behaviors. The contribution of habit and information-seeking behavior across behaviors were confirmed, while the influence of income, minor, objective norm, perception of food risks, trust, perceived behavioral control, and intention was statistically significant but inconsistently differed between behaviors. The independent contributions of gender, age, education, subjective norm, and attitude were negligible. This paper’s findings offer evidence to highlight the role of volitional predictors to anticipate safe food-handling behaviors to suggest suitable policy interventions to reinforce the last line of heath defense in the household, especially in the context of the COVID-19 pandemic.